NeoCov Variant History, Symptoms, Cause, &Treatment - N.Sriram; S.Kameshwaran; DS Asok kumar; RD Jai Kumar (International Journal of Allied Medical Sciences and Clinical Research, 2022)
Scientists in Wuhan, China, the site of the first COVID-19 case, have issued a warning about a new kind of Coronavirus known as NeoCov. It was originally detected in Saudi Arabia in 2012 and is linked to the MERS-Coronavirus, a virus that is related to SARS-CoV-2. According to the findings, NeoCov may have a significant risk of infection. According to Russian news outlet Sputnik, the NeoCov Variant has a high infection and mortality rate (one out of every three fatalities), posing a large risk of fatality when combined with SAS-high CoV-2’s transmission rate, making it a potentially lethal epidemic. MERS-Cov, according to the World Health Organization (WHO), is part of a wide family of coronaviruses that may cause a variety of illnesses, including the common cold and SARS (Severe Acute Respiratory Syndrome). Neo-Cov is not a new variety of Covid-19. It’s a coronavirus strain or another kind that was initially detected in 2012 and then again during the MERS-Cov epidemic in 2015. NeoCov is not a variation of SARS-CoV-2, the virus that causes Covid-19 symptoms in people, like Delta or Omicron. It’s a different kind of new coronavirus.